Resource Geology - Resource Geology (Wiley, 2026)
Resource Geology, an official journal of the Society of Resource Geology, publishes research dealing with economic geology, geochemistry and environmental geology with an emphasis on earth sciences of metallic and non-metallic mineral deposits in Asia, Oceania, and the circum-Pacific region, as well as other parts of the world.
FI 0.46
Q3
Keywords: Earth; Space & Environmental Sciences; Economic & Applied Geology; Geología aplicada; Economía; Acuerdos transformativos; Transformative agreements; Geología de recursos; Geoquímica; Medio ambiente; Ciencias de la tierra; Minerales